PHILOSOPHICAL SCIENCES IN THE SYSTEM OF POSTMODERN CULTURE - Кадникова, Л. В.; Мокляк, Л. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
The article examines the social- cultural function of philosophical sciences in the education process in the conditions of postmodern culture